Genetic control of the lateral petal shape and identity of asymmetric flowers in mungbean (Vigna radiata L.) - Li, Xin; Sun, Mingzhu; Jia, Yahui; Qiu, Dan; Peng, Qincheng; Zhuang, Lili (Frontiers in Plant Science, 2022)
Broad diversity of flowers in legume provides a good system to investigate development and evolution of floral symmetry in higher plants. Many studies have demonstrated a conserved mechanism controlling development of zygomorphic flower during last decades. However, the molecular basis of how asymmetric flower established is largely unknown. In this study, we characterized mutants named keeled wings (kw) in mungbean (Vigna radiata L.), which is a legume species with asymmetric flowers. Compared to those in the wild type plants, the lateral petals were ventralized in the kw mutants. Map-based cloning showed that KW was VrCYC3 gene in mungbean, the ortholog of Lotus japonicus CYC3 (LjCYC3) and Pisum sativum CYC3 (PsCYC3). In addition, another two CYC-like genes named VrCYC1 and VrCYC2 were identified from mungbean genome. The three CYC-like genes displayed distinct expression patterns in dorsal, lateral and ventral petals. It was found that VrCYC3 was located in nucleus. Further analysis showed that VrCYC3 had transcription activity and could interact with VrCYC1 and VrCYC2 in yeast cell. Moreover, the deletion of two amino acid residues in the R domain of VrCYC3 protein could decrease its interaction with VrCYC1 and VrCYC2 proteins. Our results suggest that CYC3 orthologs play conserved roles determining the lateral petal shape and identity of zygomorphic flower as well as asymmetric flower in legumes.